2020
DOI: 10.3389/fpsyg.2020.575328
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation Hypothesis of Sleep

Abstract: Sleep is a fundamental property conserved across species. The homeostatic induction of sleep indicates the presence of a mechanism that is progressively activated by the awake state and that induces sleep. Several lines of evidence support that such function, namely, sleep need, lies in the neuronal assemblies rather than specific brain regions and circuits. However, the molecular mechanism underlying the dynamics of sleep need is still unclear. This review aims to summarize recent studies mainly in rodents in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 162 publications
1
30
0
Order By: Relevance
“…The research above suggests that calcium promotes sleep in mice (Tatsuki et al 2016). Further studies have indicated the involvement of sleep-promoting kinase phosphorylation, like CaMK2 phosphorylation, which is downstream from the calcium pathway (Ode and Ueda, 2020).…”
Section: Calcium Makes Mice Sleepmentioning
confidence: 90%
“…The research above suggests that calcium promotes sleep in mice (Tatsuki et al 2016). Further studies have indicated the involvement of sleep-promoting kinase phosphorylation, like CaMK2 phosphorylation, which is downstream from the calcium pathway (Ode and Ueda, 2020).…”
Section: Calcium Makes Mice Sleepmentioning
confidence: 90%
“…It is thought that protein phosphorylation and sleep-wake cycles have bidirectional mutual effects on each other. CaMKIIα/CaMKIIβ, SIK3 and ERK1/ERK2 have been identified as sleep-promoting kinases ( Ode and Ueda, 2020 ). Phosphoproteomic studies indicated that SIK3 appears to induce a comparable phosphoproteomic profile to that caused by sleep deprivation, and the dynamics of CaMKII activation correlate well with the expected accumulation of sleep need.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, the exact molecular nature of Process S and the molecular substrates that underpin and control sleep still remain almost entirely unknown. Furthermore, whilst the two-process model provides an accurate behavioural level description of the sleep-wake cycle, the molecular basis of the interaction between the sleep and circadian system that acts to drive sleep has yet to be elucidated (Ode and Ueda, 2020). However, recent studies have highlighted the possible role of the synaptic phosphoproteome in sleep induction and regulation, as synaptic protein phosphorylation has been found to correlate with high levels of sleep pressure, and thus sleep itself.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the salt-inducible kinase, SIK3 is proposed to mediate these synaptic phosphoprotein changes (Brüning et al, 2019;Wang et al, 2018). Whilst providing the foundation for the intriguing hypothesis that the molecular basis of sleep induction may be encoded at the level of the synaptic phosphoproteome, currently these studies cannot establish causation, and instead only demonstrate a correlation between synaptic protein phosphorylation and sleep (Ode and Ueda, 2020). Furthermore, whether sleep-promoting external inputs such as light, that operate independently of sleep pressure and/or sleep history, also impact the synaptic phosphoproteome is entirely unknown.…”
Section: Introductionmentioning
confidence: 99%